VERTICAL HOUSING DESIGN WITH BIOPHILIC APPROACH IN EAST JAKARTA - Kevin Christian Immanuel; Rachmat Taufick Hardi; Hanugrah Adhi Buwono (Lakar: Jurnal Arsitektur, 2023)
The city of Jakarta as the capital city of Indonesia is one of the areas that many people live in. The city of Jakarta is also the center of a rapidly growing economy in Indonesia, so that a large number of residents decide to settle there. This causes the issue of significant population growth every year. This population growth causes an increase in the need for a dwelling. With increasingly limited land in Jakarta, vertical housing such as apartments can be a solution to provide a residence with a large capacity on limited land. In addition, the location of the land to be discussed is in Jakarta Garden City, Cakung, East Jakarta. The East Jakarta area itself is an industrial area, this can be seen from the location of the Jakarta Garden City site which is surrounded by industrial buildings such as factories and warehouses. With the existence of industrial activities around the location causing the environment to be less good due to pollution. Therefore, the application of biophilic design as a design theme can be a solution to this environmental issue. Biophilic itself is a concept that focuses on the relationship between humans and nature or the surrounding environment. In the design process, a data search was conducted that focused on 14 biophilic patterns, which would become a reference for the design. The application of this biophilic concept is expected to reduce the negative impact of pollution produced by industrial areas around the site. The biophilic concept also implements greenery into its design so that it is hoped that this greenery can act as a filter that captures pollution and cools the surrounding air.